HARMONISASI REGULASI PENGELOLAAN RUMAH SUSUN: MITIGASI KONFLIK PENAGIHAN IPL MELALUI PENDEKATAN RESTORATIVE JUSTICE DAN HUKUM PERLINDUNGAN KONSUMEN - Robert L Simanungkalit; Parsaoran Situmorang; Selvira Paulina Ananda; Jopie Tommy Rompas; Ruby W H Oktolina Samosir (Jurnal Humaniora & Sosial Sains, 2026)
Conflicts between the Management Board and apartment unit owners regarding the collection of Environmental Management Fees (IPL) often create prolonged social and legal tensions. This study aims to analyze the legitimacy of these actions through the lens of the Consumer Protection Law, contract law, and criminal law using normative juridical research methods. This study analyzes the urgency of harmonizing regulations on apartment management by integrating the principles of Restorative Justice and the Consumer Protection Law (UUPK). Through normative juridical research methods, it was found that unilateral termination is a form of abuse of power relations that violates Article 18 of the UUPK and consumer human rights. The study shows that unilateral termination is a form of abuse of power relations that violates basic consumer rights and contradicts the principle of propriety, so that the clause in the House Rules that legitimizes this practice is declared null and void. As a mitigation solution, this study offers a Restorative Justice paradigm that prioritizes dialogue and relationship restoration to avoid the practice of vigilantism or eigenrichting which carries criminal risks. This study offers a new paradigm in conflict resolution through penal mediation (restorative justice) and a relationship restoration approach, to avoid the practice of vigilantism (eigenrichting). The results of the study recommend the need for policy reform that prioritizes dialogue and proportional sanctions to create harmony in life in flats.